Optimización del trozado de fustes en el nivel de unidad de manejo forestal - Yapura, Pablo; Sañudo, Gastón; Keller, Aldo Esteban; Fassola, Hugo Enrique; Crechi, Ernesto Hector; Winck, Rosa Ángela; Barth, Sara Regina; Caraballo, Horacio (Facultad de Ciencias Forestales, Universidad Nacional de Misiones., 2022)
In planning forest harvests the bucking optimization problem arises at tree-level as well as stand and forest management unit-level. In a former project, Dynamic Programming has been coded in spreadsheets for obtaining optimal buching patterns at tree-level for major species in NE Argentina. At the stand and forest-level the problem has been formulated as a linear programming, master problem, and using a longest path algorithm for sub-problem, bucking pattern generation. GLPK and Java were used for coding OptimEsus, a software tool aimed at solving problems at these levels. A three stand problem was solved as a prototypical example.